Centro de arte e cultura dos povos indígenas em Manaus - Amazonas - Picanço, Natacha Freitas (Brasil, 2022)
The present study has as its general objective to propose the project of an Amazonian Art and Culture Center, in the city of Manaus-Amazonas, which has as its starting point to be an element of valorization and promotion of the culture and history of the indigenous people, that meets to the demands of tourism and local commerce, which is characterized by respecting current legislation and expanding the opportunity to bring knowledge and entertainment to the city's residents and visitors. This theme unfolds in the specific objectives that aim to investigate the history of the indigenous trajectory in Brazil, understanding its important contribution to society, learning the functioning of architectural objects such as this one proposed from case studies. This work is justified by the science of the real need for the establishment of an Indigenous Culture and Art Center, recognizing the importance of a place that offers conditions for strengthening, dissemination, promotion and debate on indigenous culture. This research has applied character, aiming to use knowledge that demonstrate the influence of architecture in the creation of spaces that aggregate knowledge, access to art and promote tourism and local crafts, in addition to the exploratory aspect since it sought to better understand the importance of a valorization center of the regional culture. The results show that architecture can contribute Architecture can positively interfere in the development of a project that promotes awareness and appreciation of the indigenous cause through the adoption of design criteria that are applied since the choice of the program, so as to integrate several scenes of interest. to the specification of regionally identifiable materials.